(untitled) (Research, Society and Development, 2022)
Asthma is a chronic disease caused by contact with an allergen that induces an inflammatory response that affects part of the respiratory tract in a genetically predisposed individual. Although its concepts are well known by most of the current scientific community, the dissemination of new studies occurs constantly, which contributes to the updating of the theme, while the addition of new information occurs. Therefore, the objective of this study was to review the literature on the main characteristics of asthma, highlighting its pathophysiological aspects. For this, an integrative review was carried out using secondary data, obtained through the digital bibliographic databases PubMed, STM (Science Translational Medicine) and SciELO (Scientific Electronic Library Online), during the period from September to October 2022. exposition of the results obtained, Table 1 was constructed, which summarizes the main works used for this study. Likewise, the objective of this work was further explored in the topic of “Discussion”, organized based on the selected sources. Thus, the information presented in this review can be taken into account by future researchers who wish to update themselves on the topic of asthma, focusing on its pathophysiological aspects.